Pengaruh Digital Marketing terhadap Peningkatan Volume Penjualan Kamar di The Patra Bali Resort & Villas - Luh Gede Putri Sari P; Suhardi Suhardi (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to find out and analyze the influence of digital marketing consisting of Websites, Social Media and Online Travel Agents (OTA), on the volume of sales increase in the recovery period at The Patra Bali Resort & Villas. This research uses quantitative data types and takes the form of associative research. The population in this study is all consumers of The Patra Bali Resort & Villas. The samples in this study are included in the category of non-probability sampling with the purposive sampling method. The sample criteria in this study were consumers (tourists and/or visitors) of The Patra Bali Resort & Villas who made transactions (bookings) through digital marketing channels, namely: email, social media (IG) and OTA). The method of data collection is carried out by distributing questionnaires. The data analysis method uses multiple linear regression analysis.Â  The results of the analysis in this study show that digital marketing via email has a positive effect on the volume of sales increase at The Patra Bali Resort & Villas. This means that the higher and more effective the implementation of digital marketing via email, the more it will affect the increasing volume of sales at The Patra Bali Resort & Villas. Digital marketing through social media (Instagram) positively affects the volume of sales increase at The Patra Bali Resort & Villas. This means that the more effective the implementation of digital marketing via email, the more it will increase the volume of sales increase. Digital marketing through Online Travel Agents positively affects the volume of sales increase at The Patra Bali Resort & Villas. This means that the higher and more effective the application of Online Travel Agent, the more it will affect the increasing volume of sales at The Patra Bali Resort & Villas.